Effectiveness of Information Technology Utilization - Muh. Darwis; Mutmainnah Mutmainnah; Jamaluddin Jamaluddin (Program Pascasarjana Universitas Negeri Makassar, 2024)
Information technology allows offices to manage information and communication more effectively and efficiently. By using information technology, offices can optimize the data management process. This study aims to determine the effectiveness of the use of information technology in employees of PT. Midi Utama Indonesia Tbk Makassar, and to find out the supporting and inhibiting factors for the effectiveness of the use of information technology in employees of PT. Midi Utama Indonesia TBk Makassar. This research uses a qualitative method, therefore in order to achieve a research objective, data collection techniques are used, namely observation, interviews, and documentation. The informants of this research were 5 employees of PT. Midi Utama Indonesia Tbk Makassar. The results of this study show that the effectiveness of the use of information technology in employees of PT. Midi Utama Indonesia Tbk Makassar can be seen from the indicators that hardware, software and brainware are